Pemberdayaan Kelompok Budidaya Jamur Tiram Putih (Pleurotus ostreatus) Melalui Penerapan Teknologi dan Inovasi dalam Peningkatan Produksi, Diversifikasi Produk, Branding Produk, dan Pemanfaatan Limbah - Martan, Sumartan; Jumadi, Oslan; azwar, Azwar; Wahyuddin, Nur Rahmah; syamsidah, Syamsidah; Suryaningsih, Nur Anny; taufiq, Taufiq (Universitas Muhammadiyah Sidenreng Rappang, 2023)
This service describes a community empowerment initiative through service to the oyster mushroom cultivation group in Tasiwalie Village. This empowerment approach focuses on the application of technology and innovation in oyster mushroom cultivation with the aim of increasing production, diversifying processed products, product branding and waste management. By integrating modern technology such as sensors, automatic irrigation systems, and temperature and humidity control techniques in kumbung, oyster mushroom production is increased significantly. In addition, through training and business assistance, the oyster mushroom food business group is provided with assistance and training regarding product diversification and effective branding strategies to increase the competitiveness of its products in local and regional markets. In addition, waste management from the cultivation process is converted into high-value resources such as charcoal briquettes. The result is an increase in the income of cultivation groups, improvement in community welfare, and the creation of a sustainable model of rural economic empowerment. This dedication makes a real contribution in strengthening local economic resilience while reducing environmental impacts, thereby creating a positive outlook towards sustainable agricultural development.